Evidence for a GABAergic system in rodent and human testis: local GABA production and GABA receptors - Geigerseder, C. (2003)
The major neurotransmitter of the central nervous system, gamma-aminobutyric acid (GABA), exerts its actions through GABA(A), GABA(B) and GABA(C) receptors. GABA and GABA receptors are, however, also present in several non-neural tissues, including the endocrine organs pituitary, pancreas and testis. In the case of the rat testis, GABA appears to be linked to the regulation of steroid synthesis by Leydig cells via GABA(A) receptors, but neither testicular sources of GABA, nor the precise nature of testicular GABA receptors are fully known. We examined these points in rat, mouse, hamster and human testicular samples. RT-PCR followed by sequencing showed that the GABA-synthesizing enzymes glutamate decarboxylase (GAD) 65 and/or GAD67, as well as the vesicular GABA transporter vesicular inhibitory amino acid transporter (VIAAT/VGAT) are expressed. Testicular GAD in the rat was shown to be functionally active by using a GAD assay, and Western blot analysis confirmed the presence of GAD65 and GAD67. Interstitial cells, most of which are Leydig cells according to their location and morphological characteristics, showed positive immunoreaction for GAD and VIAAT/VGAT proteins. In addition, several GABA(A) receptor subunits (alpha1-3, beta1-3, gamma1-3), as well as GABA(B) receptor subunits R1 and R2, were detected by RT-PCR. Western blot analysis confirmed the results for GABA(A) receptor subunits beta2/3 in the rat, and immunohistochemistry identified interstitial Leydig cells to possess immunoreactive GABA(A) receptor subunits beta2/3 and alpha1. The presence of GABA(A) receptor subunit alpha1 mRNA in interstitial cells of the rat testis was further shown after laser microdissection followed by RT-PCR analysis. In summary, these results describe molecular details of the components of an intratesticular GABAergic system expressed in the endocrine compartment of rodent and human testes. While the physiological significance of this peripheral neuroendocrine system conserved throughout species remains to be elucidated, its mere presence in humans suggests the possibility that clinically used drugs might be able to interfere with testicular function.